1972
DOI: 10.1103/physrevlett.28.1133
|View full text |Cite
|
Sign up to set email alerts
|

Localized-to-Itinerant Electron Transitions in Rare-Earth Cobaltates

Abstract: IVTossbauer studies show that cobalt ions in LaCo0 3 exist predominantly in the low-spin Co 111 state at low temperatures and partially transform to the high-spin Co 3+ state up to 200 K. Above 200 K, Co 11 and Co 4+ ions are formed by the transfer of d electrons from Co 3+ to Co 111 ; Co 3+ ions completely disappear at the first-order localized-to~itinerant electron transition temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
2

Year Published

1979
1979
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 10 publications
3
15
0
2
Order By: Relevance
“…Using soft-X-ray absorption spectroscopy (XAS), the latter authors conclude that LaCoO 3Àd is in the low-spin state at low temperatures, and that from 550 K to 630 K there is a gradual transition to a mixed-spin state, in agreement with previous studies [13,14]. Unlike the former groups [13,14], they found no evidence for charge disproportionation from 80 K to 630 K. Casalot et al [16] studied GdCoO 3 in the temperature range 77-1200 K using combined DTA, XRD, magnetic susceptibility, electric conductivity and thermoelectric power investigations. They stated that the properties of GdCoO 3 fit well to Goodenough's [17] localized electron model.…”
Section: Literature Surveysupporting
confidence: 80%
See 2 more Smart Citations
“…Using soft-X-ray absorption spectroscopy (XAS), the latter authors conclude that LaCoO 3Àd is in the low-spin state at low temperatures, and that from 550 K to 630 K there is a gradual transition to a mixed-spin state, in agreement with previous studies [13,14]. Unlike the former groups [13,14], they found no evidence for charge disproportionation from 80 K to 630 K. Casalot et al [16] studied GdCoO 3 in the temperature range 77-1200 K using combined DTA, XRD, magnetic susceptibility, electric conductivity and thermoelectric power investigations. They stated that the properties of GdCoO 3 fit well to Goodenough's [17] localized electron model.…”
Section: Literature Surveysupporting
confidence: 80%
“…These authors showed that cobalt ions are in a low-spin state at low temperatures and partially transform to a high-spin state Co 3+ t 4 2g e 2 g up to 200 K. Their findings are, however, in conflict with the results from Abbate et al [15]. Using soft-X-ray absorption spectroscopy (XAS), the latter authors conclude that LaCoO 3Àd is in the low-spin state at low temperatures, and that from 550 K to 630 K there is a gradual transition to a mixed-spin state, in agreement with previous studies [13,14]. Unlike the former groups [13,14], they found no evidence for charge disproportionation from 80 K to 630 K. Casalot et al [16] studied GdCoO 3 in the temperature range 77-1200 K using combined DTA, XRD, magnetic susceptibility, electric conductivity and thermoelectric power investigations.…”
Section: Literature Surveysupporting
confidence: 48%
See 1 more Smart Citation
“…The ground state of LaCoO 3 with Co 3+ (3d 6 ) ions is a charge transfer type insulator with no magnetic order. The magnetic susceptibility increases exponentially with increasing temperature to reach a maximum near 100 K. This transition was initially explained as a spin state transition from a low spin nonmagnetic state (t 6 2g , S = 0, LS) to a high spin state (t 4 2g e 2 g , S = 2, HS) [1][2][3][4] but later the existence of an intermediate spin state (t 5 2g e 1 g , S = 1, IS) was proposed. The spin state transition originates from a competition between crystal field splitting energy and interatomic Hund exchange coupling energy.…”
Section: Introductionmentioning
confidence: 98%
“…The x = 0.4 composition shows significant change at around 500 8C. The reason is assumed due to a spin transition from the smaller ionic radius of the low spin Co 3+ ion (r = 0.0545 nm) to the high spin Co 3+ ion (r = 0.061 nm) with increasing temperature [12,13], which leads to an increase in TEC [14]. The substitution of Co by Fe induced to decrease TEC values.…”
Section: Resultsmentioning
confidence: 89%